2020
DOI: 10.1002/adom.202001627
|View full text |Cite
|
Sign up to set email alerts
|

Soft Lithography for Manufacturing Scalable Perovskite Metasurfaces with Enhanced Emission and Absorption

Abstract: Organic–inorganic hybrid perovskites have emerged in recent years as a promising alternative to silicon solar cells and other optoelectronic devices, mostly due to their high photon yields, long carrier lifetime, adjustable bandgap, and other merits. While patterning photonic nanostructures onto their inorganic counterparts is well established to augment their capabilities, lack of compatibility with conventional lithography techniques hinders the implementation of those principles with perovskites. Hereby, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…We will also show that the presence of roughness and defects generate fluctuations and hot spots that modify the luminescence. Although the structures have been fabricated on a sub-millimeter scale, they can also be created on much larger scales using, for instance, interference lithography or soft lithography 42,43 .…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will also show that the presence of roughness and defects generate fluctuations and hot spots that modify the luminescence. Although the structures have been fabricated on a sub-millimeter scale, they can also be created on much larger scales using, for instance, interference lithography or soft lithography 42,43 .…”
Section: A Introductionmentioning
confidence: 99%
“…Although structures have been fabricated on a submillimeter scale, they can also be created on much larger scales using, for instance, interference lithography or so lithography. 42,43 B Techniques and methods…”
Section: A Introductionmentioning
confidence: 99%
“…33 The beneficial impact of photonic structuration on optical performances of PSCs has been highlighted in terms of light trapping and harvesting capacity, thanks to the fine tuning capacity of the difference of optical constants directly at the interface; assembled PV devices are also shown to present improved properties of charge injection, transportation, and collection efficiency. 15,22,23 The exact morphology, structure, and organization degree of such TiO 2 "scaffolds" as well as their processing method-ologiesthat may involve soft (block-polymer templating) 16 and hard (solid spheres assembly) 17 lithographic approaches, nanoimprinting processes, 13,18,19 anodization treatments, 34 etc.have been further discussed as these crucially influence both optical and electronic properties of the PSCs. 15,22,23 In comparison with unstructured mesoporous layers consisting of randomly packed spherical TiO 2 nanoparticles, one-(1D), two-(2D), and three-dimensional (3D) photonically structured layers specifically allow not only for increased and more organized porosity, achieving more controlled perovskite infiltration, but also for improved carrier transportation and recombination behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methodologies of photonic structuration have been reported in the literature, all aiming at optimizing the light–matter interactions from appropriate texturing of a photoactive material or device constituent. Various top-down and bottom-up approaches and protocols, including soft templating with polymer surfactants, nanosphere lithography, or nanoimprinting, , have been used for photonically structuring the photoactive material with the perspective of enhancing performances of the PV devices in terms of light harvesting, photocurrent generation, and mitigation of lead content in PSCs. Noteworthily, the recent simulation-based study conducted by Schmager et al has shown that the design of optimized nanophotonic perovskite layers could lead to a 5–6% increased photocurrent together with enhanced light harvesting efficiency …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation